RELATIONSHIP OF PERSONAL FACTORS KNOWLEDGE WITH RISKY BEHAVIOR ON CEREBROVASCULAR DISEASE AMONG THE ELDERLY WITH HYPERTENSION - คำแน่น, กุลินทร; โพธิ์ชัย , ศิวิไล; พรหมภักดี , ธนัญญา; พรมเพ็ญ , ปาลิตา (Primary Health Care Journal (Northeastern Edition), 2023)
The purposes of this cross-sectional research were to examine the relationship between personal factors knowledge with risky behavior and cerebrovascular disease among the elderly with hypertension. The sample consisted of 476 elderly people with high blood pressure collected by simple random sampling at Ban Nong Waeng Health Promoting Hospital, Phon Khwao Sub-district, Mueang District, Sisaket Province. The research instruments are knowledge tests and questionnaires by the researcher, with reliability of 0.87 and 0.94. Statistics used for data analysis included frequency, percentage, mean, standard deviation, chi-square, and Pearson’s product moment correlation. The research results found that from a random sample of 476 elderly people with high blood pressure, they had a level of knowledge about cerebrovascular disease at a moderate level of (72.20%) (SD = 0.40) and a level of risk behavior for cerebrovascular disease at a moderate level of mean score 2.04 (SD = 0.67). Factors associated with risky behaviors for cerebrovascular disease in elderly people with high blood pressure include gender, marital status, education level, occupation, and average monthly income. Immediate relatives suffering from chronic illnesses and knowledge about cerebrovascular disease in terms of stress, It is associated with risky behaviors associated with cerebrovascular disease in elderly people with high blood pressure. Statistically significant at the.05 level.